A new passivation scheme for the performance enhancement of black silicon solar cells. (September 2019) - Ramos, C.; Verduzco-López, Y.; Álvarez-Macías, C.; Sanchez-Juarez, A.; Dutt, A.; Santana, G.
Graphical abstract: Highlights: Formation of black silicon solar cells was carried using out using etching methods. MACE process using two different metals was applied to do a nanometric etching on pyramidal surfaces. A double stack layer of pm-Si/SiNx was employed on the surface of the device and was treated in an ammonia plasma. I–V measurements and EQE measurements showed better performance of the solar cell device proposed in this work. Abstract: It is well known that, in c-Si solar cells, the surface treatments are very important and have great relevance in the final efficiency of the devices. Black silicon solar cells are the terminology commonly used for solar cells with different grades of nanometric surface texturizations. In this work, we prepared silicon solar cells with a diverse grade of chemical surface treatment (alkaline etch and MACE treatment), plasma annealing (ammonia and hydrogen) with silicon-rich silicon nitride as passivation and antireflection coating. Spectral response, surface reflectance, and I–V measurements were carried out to obtain the final performance of the cell fabricated in the present work. From all the devices fabricated in the present work, the best results were obtained for the structure where the double stack layer (pm-Si/SiNx) was used as the passivation scheme, and plasma treatment was carried out in ammonia atmosphere as in comparison to existing conventional passivation schemes.